PEMANFAATAN, PEMELIHARAAN DAN PENGEMBANGAN USAHA PETERNAKAN KAMBING SECARA OPTIMAL PADA KELOMPOK PETERNAK KAMBING JOYO ABADI - Aju Tjatur Nugroho Krisnaningsih (Publisher UPT P2M Politeknik Negeri Malang, 2015)
Community service groups goat breedersinthe village Bumiaji aims to improve theknowledge and skills of farmers in the utilization and processing of potential sources of local feed ingredients, exploitation superior breeding stock, then capable and skilled in yogurt fermented dairy product processing, sewage treatment lives tockinto organic fertilizer to increase the income and welfare of farmers. Delivery of content and methods of activity in the form of counseling, training, demoplot, assistance and program evaluation. The results of this program showed a high response from the community goat breeders for proactive follow the program in all the activities. It can be concluded that this service programs have a positive impacton the environment that partners provide solutions or alternative solutions to problems faced by farmers int he villages and the surrounding community.